2005
DOI: 10.1360/04wb0087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of virus removal in MBR using coliphages T4

Abstract: A membrane bioreactor (MBR) with gravity drain was tested for domestic wastewater for 65 days. Results showed that the effluent quality was excellent, and met with the reuse water standard of China (GB/T 18920-2002). Virus removal in the membrane separation process was investigated by employing coliphages T4 as a tracer. Two microfiltration membrane modules, with pore sizes of 0.22 and 0.1 m, were used to investigate their effects on virus rejection at the transmembrane pressure of 8.5 kPa. It was found that 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Membrane rejection was an essential supplement to biomass effect, which is particularly the case when the membrane was fouled, allowing the effluent SC to be less than 10 PFU$mL -1 . The fouling layer-enhanced virus retention has also been reported by a few other researchers, using phage T4 [42][43][44], phage f2 [44], etc., as indicators. Further study by Wu et al [41] revealed that gel layer played a more important role in SC rejection than cake layer, especially at higher filtration fluxes (Fig.…”
Section: Pathogen Removalsupporting
confidence: 67%
“…Membrane rejection was an essential supplement to biomass effect, which is particularly the case when the membrane was fouled, allowing the effluent SC to be less than 10 PFU$mL -1 . The fouling layer-enhanced virus retention has also been reported by a few other researchers, using phage T4 [42][43][44], phage f2 [44], etc., as indicators. Further study by Wu et al [41] revealed that gel layer played a more important role in SC rejection than cake layer, especially at higher filtration fluxes (Fig.…”
Section: Pathogen Removalsupporting
confidence: 67%
“…As for the behavior of viruses, the related information is very limited. Proper treatment before being discharged into receiving water bodies has become of increasing importance since the worldwide outbreak of SARS and Avian Influenza Virus in recently years [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional wastewater treatment technology cannot completely remove or inactivate enteric viruses. Recently, membrane bioreactor (MBR) has received increasing attention in the past two decades as advanced wastewater treatment alternatives [3][4][5] . MBR is a modification of the activated sludge process in which separation of solids is achieved without the requirement of a secondary clarifier.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [25] reported that gel layer contributed to the removal of somatic coliphage removal, more so at a higher permeate flux. High removals of T4 coliphage have been reported and partly attributed to the formation of a cake layer formed on membrane surface [26][27][28][29]. Shirasaki et al carried out filtration experiments in a coagulation-MF system and concluded that irreversible fouling played a more important role than reversible fouling in enhancing virus removal [30].…”
Section: Introductionmentioning
confidence: 99%